2015
DOI: 10.1371/journal.pone.0134926
|View full text |Cite
|
Sign up to set email alerts
|

Using Satellite Tracking and Isotopic Information to Characterize the Impact of South American Sea Lions on Salmonid Aquaculture in Southern Chile

Abstract: Apex marine predators alter their foraging behavior in response to spatial and/or seasonal changes in natural prey distribution and abundance. However, few studies have identified the impacts of aquaculture that represents a spatially and temporally predictable and abundant resource on their foraging behavior. Using satellite telemetry and stable isotope analysis we examined the degree of spatial overlap between the South American sea lion (SASL) and salmon farms, and quantify the amount of native prey versus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 70 publications
3
27
0
4
Order By: Relevance
“…Potential food sources may include crustaceans and planktivorous fish from Patagonian fjords representing the last whereabouts of the investigated sei whales. Elsewhere in Chilean Patagonia, similar values were recorded for this species(Sepúlveda et al, 2015) and other planktivorous fish(Mayr et al, 2011) (Figure 4). Patagonian sprat (Sprattus fuegensis), an important forage fish in the Patagonian marine ecosystems, provided δ 15 N values of 14.5 ± 0.4‰ and δ 13 C values of −16.6 ± 0.8‰ in the Aysén region close to where the stranded sei whales were found (44 − 47°S;Montecinos, Castro, & Neira, 2016).…”
supporting
confidence: 75%
See 1 more Smart Citation
“…Potential food sources may include crustaceans and planktivorous fish from Patagonian fjords representing the last whereabouts of the investigated sei whales. Elsewhere in Chilean Patagonia, similar values were recorded for this species(Sepúlveda et al, 2015) and other planktivorous fish(Mayr et al, 2011) (Figure 4). Patagonian sprat (Sprattus fuegensis), an important forage fish in the Patagonian marine ecosystems, provided δ 15 N values of 14.5 ± 0.4‰ and δ 13 C values of −16.6 ± 0.8‰ in the Aysén region close to where the stranded sei whales were found (44 − 47°S;Montecinos, Castro, & Neira, 2016).…”
supporting
confidence: 75%
“…Clearly, more baseline data obtained in future studies could improve evaluating migration patterns using southern sei whale baleen isotope records. Additionally, values of potential prey items are given: Sprattus fuegensis (Montecinos et al, 2016;Sepúlveda et al, 2015), small planktivorous fish (Mayr et al, 2011), Munida gregaria (Pérez-Barros et al, 2010), euphausiids (Mayr et al, unpublished;Montecinos et al, 2016), and copepods (Montecinos et al, 2016). In the latter study, the baleen plates of F I G U R E 4 δ 15 N versus δ 13 C values of baleen plates (small filled circles) corrected for trophic fractionation (Δ 13 C and Δ 15 N, respectively, from Borrell et al, 2012).…”
Section: Possible Causes For Cyclic Variationsmentioning
confidence: 99%
“…Sepúlveda et al . () showed that SASL, which previously consumed a high proportion of salmon (Muñoz et al . ), changed their diet during this period, likely in response to the decrease in salmon availability.…”
Section: Discussionmentioning
confidence: 99%
“…Along the Pacific coast, recent studies using time‐depth recorders and satellite tags also indicated that SASL from southern Chile displayed a mesopelagic‐benthic diving strategy (Sepúlveda et al . , Hückstädt et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Sepúlveda et al . () examined the degree of spatial overlap between the South American sea lions and salmon farms using satellite telemetry and stable isotope analysis, and quantified the amount of native prey versus farmed salmonids in their diets. The most important prey were farmed salmonids, with an estimated median of 19.7% and 15.3% for hair and skin, respectively.…”
Section: Salmon Farming Environmental Impacts During the Marine Fattementioning
confidence: 99%